The Impact of Silica Nanoparticles on the Properties of WPI/CMC Biocomposite Films for Packaging Applications - Mukhlishien; Syahiddin DS; Medyan Riza; Azwar (Jurnal Serambi Engineering, 2024)
WPI/CMC biocomposite films reinforced with silica offer a biodegradable alternative to traditional plastics. The primary aim was to assess the impact of silica reinforcement on the films' physical, mechanical, water barrier, and thermal properties, which are crucial for packaging applications. Silica nanoparticle reinforcement significantly enhanced the tensile strength of WPI/CMC biocomposite films, reaching a maximum of 27.07 MPa at a 7% silica concentration. This enhancement in tensile strength came at the cost of reduced elongation, which decreased from 26.48% to 8.32%. The thickness of WPI/CMC biocomposite films with silica addition ranged from 0.126 to 0.371 mm. Silica incorporation significantly reduced water absorption, with a decrease from 83.23% to 63.33%. Tensile strength varied significantly, ranging from 2.02 to 27.07 MPa. Similarly, the elongation values ranged widely, from 7.42% to 26.48%. Thermal properties increased with the increase of silica. The morphology of the biocomposite films with 1%, 3%, 5%, 7%, and 9% silica additions exhibited uneven surfaces. The morphology of the biocomposite films was also affected by silica incorporation. The addition of silica nanoparticles resulted in uneven surfaces, which may influence the film's barrier properties and overall performance. Silica nanoparticle reinforcement offers a promising approach to enhance the mechanical properties of WPI/CMC biocomposite films. However, careful optimization of silica concentration is crucial to balance strength and flexibility.